2014
DOI: 10.1103/physrevb.90.245305
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of spin-orbit and hyperfine interactions in dynamical nuclear polarization in semiconductor quantum dots

Abstract: We theoretically study the interplay of spin-orbit and hyperfine interactions in dynamical nuclear polarization in two-electron semiconductor double quantum dots near the singlet (S) -triplet (T+) anticrossing. The goal of the scheme under study is to extend the singlet (S) -triplet (T0) qubit decoherence time T * 2 by dynamically transferring the polarization from the electron spins to the nuclear spins. This polarization transfer is achieved by cycling the electron spins over the S − T+ anticrossing. Here, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The DDNP technique depends on the interaction between the two-electron spin singlet |S = (|↑↓ − |↓↑ )/ √ 2 and spin triplet |T − = |↓↓ mediated by the hyperfine coupling to lattice nuclear spins [28]. It was shown that spin-orbit * Correspondence to: P.Collard@USherbrooke.ca † Correspondence to: mscarro@sandia.gov interaction can couple these two states as well [29], impacting the ability to perform a DDNP by providing an alternate channel to dissipate angular momentum [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The DDNP technique depends on the interaction between the two-electron spin singlet |S = (|↑↓ − |↓↑ )/ √ 2 and spin triplet |T − = |↓↓ mediated by the hyperfine coupling to lattice nuclear spins [28]. It was shown that spin-orbit * Correspondence to: P.Collard@USherbrooke.ca † Correspondence to: mscarro@sandia.gov interaction can couple these two states as well [29], impacting the ability to perform a DDNP by providing an alternate channel to dissipate angular momentum [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…As such, for ε 0,S → S,G → S(0, 2) and for ε 0,S → S(0, 2),G → S, where statesS andG are often referred as the hybridized singlet states 14,15 . The Hamiltonian in the adiabatic basis {|S , |T + , |T 0 , |T − |G } transforms tõ…”
Section: Modelmentioning
confidence: 99%
“…11,12 An important question concerning the limiting factors to DNP efficiency when traversing the S − T + resonance, is whether the spin-orbit interaction (SOI) could influence DNP transfer from the electron to the nuclear spins, and consequently affect the fidelity of the singlet-triplet qubits. 13,14 In particular, a quenching of DNP has been observed when SOI exceeds the hyperfine interaction, preventing an increase in the spin decoherence time in GaAs quantum dots. 15 Recently, interferometry experiments have been able to probe the fast dynamics associated with S − T + transitions by correlating the outcomes of an ensemble of individual single shot measurements of the qubit state after LZ transitions.…”
Section: Introductionmentioning
confidence: 99%
“…The coupling of the electrons to the underlying nuclear environment plays an important role in spintronics [1] and utilization of electron spins for quantum computation [2][3][4]. More generally, the interaction between a driven electron-spin qubit and its many-body environment leads to complex dynamical phenomena which are absent if the system is assumed to be at equilibrium with its environment [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Thus, a qubit can be utilized as a probe for studying out-of-equilibrium physics in interacting quantum systems.…”
Section: Introductionmentioning
confidence: 99%